1985
DOI: 10.1111/j.1365-2818.1985.tb02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased estimation of particle density in the tandem scanning reflected light microscope

Abstract: SUMMARY The tandem scanning reflected light microscope has the property of being able to obtain information from ‘inside’ solid objects by taking a thin optical section at the focal plane of the objective lens. This plane can be focused up and down through the specimen. We describe an unbiased 3‐D counting rule for the TSRLM, which is applied to the estimation of osteocyte lacunar density in whole bone. This is shown to be an extremely efficient way of making such an estimate. Further possibilities for the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
96
0
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 10 publications
0
96
0
2
Order By: Relevance
“…Replicated data from a confocal microscope were first collected by Howard et al (1985) and a ratio regression approach was developed in Baddeley et al (1987). Konig et al (1991) found huge variations in estimates of point density A between replicated three-dimensional samples and concluded that their data (three replicates per animal) were insufficient to support quantitative conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Replicated data from a confocal microscope were first collected by Howard et al (1985) and a ratio regression approach was developed in Baddeley et al (1987). Konig et al (1991) found huge variations in estimates of point density A between replicated three-dimensional samples and concluded that their data (three replicates per animal) were insufficient to support quantitative conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…repeated 'cutting and glueing', below. Normally this has not been practical but, with the current development of the Tandem Scanning Reflected Light Microscope (Boyde et al, 1982), such replication without destruction may become feasible and effective in suitable tissues (Howard et al, 1985). Notwithstanding, quite often material specimens are sufficiently isotropic that a single extensive section will suffice, in which case a HIESP (homogeneous and isotropic ergodic stochastic process) model may be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies of airway inflammation in asthma have adopted stereological approaches [26,[28][29][30] and of these only three have used a disector to enumerate cell density. No such studies appear to have used the optical disector [31][32][33] in thick sections to measure the density of inflammatory cells in actual 3D space.…”
mentioning
confidence: 99%